Serum Trace Elements Concentrations in Patients with Restless Legs Syndrome - Félix Javier Jiménez-Jiménez; Pedro Ayuso; Hortensia Alonso-Navarro; Marisol Calleja; Mónica Díez-Fairén; Ignacio Álvarez; Pau Pastor; José Francisco Plaza-Nieto; Santiago Navarro-Muñoz; Laura Turpín-Fenoll; Jorge Millán-Pascual; Marta Recio-Bermejo; et al. (MDPI AG, 2022)
Increased brain and serum zinc levels in patients with idiopathic restless legs syndrome (idiopathic RLS or iRLS) were described when compared with controls, suggesting a possible role of zinc in the pathogenesis of this disease. However, serum magnesium, calcium, manganese, iron, and copper levels of RLS patients were similar to controls, suggesting a specific impairment of zinc-dependent metabolism in RLS. The aim of this study is to assess the serum concentrations of trace elements involved in oxidative stress or causing peripheral nerve toxicity in a large series of patients with iRLS and controls. We determined serum levels of iron, copper, manganese, zinc, magnesium, selenium, calcium, aluminium, lead, cadmium, arsenic and mercury in 100 patients diagnosed with iRLS and in 110 age- and sex-matched controls using Inductively Coupled Plasma Mass Spectrometry. Serum copper, magnesium, selenium, and calcium concentrations were significantly higher in RLS patients than in controls. These differences were observed both in men and women. There were no major correlations between serum trace metal concentrations and age at onset of RLS or RLS severity, nor was there any association with a family history of RLS or drug response. This study shows an association between increased serum concentrations of copper, magnesium, selenium, and calcium with RLS in a Spanish Caucasian population and does not confirm the previously reported increase in serum zinc concentrations in patients suffering from this disease, suggesting that the different accuracy of the analytical methods used could have influenced the inconsistent results found in the literature.